Meet Ray Epps: The Fed-Protected Provocateur Who Appears To Have Led The Very First 1/6 Attack On The U.S. Capitol (Revolver, 2021)
In order to protect the country from fictional right-wing "patriot" groups, did the FBI become an insurrectionist "patriot" movement?